Pathogenicity of Aeromonas hydrophila on the liver function of African catfish (Clarias gariepinus) - MUH MULTAZAM B. H. ABD HAKIM; HILAL ANSHARY; MUHAMMAD IQBAL DJAWAD; MUHAMMAD REZA PERDIANSYAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Abd Hakim MMBH, Anshary H, Djawad MI, Perdiansyah MR. 2025. Pathogenicity of Aeromonas hydrophila on the liver function of African catfish (Clarias gariepinus). Biodiversitas 26: 5430-5437. Aeromonas hydrophila is a major bacterial pathogen in African catfish (Clarias gariepinus) aquaculture, responsible for systemic infection, tissue damage, and high mortality. This study investigated the pathogenic effects of graded acute infections on liver function and histopathology of African catfish under controlled laboratory conditions. Seventy-two fish were allocated to three bacterial treatment groups with increasing concentrations and a control group, each with three replicates. After seven days, blood samples were analyzed for ten biochemical indicators of hepatic function, including plasma proteins, transaminases, bilirubin, bile acids, cholesterol, and liver enzymes, while histopathological examinations were conducted on liver tissues. The infection induced significant alterations in albumin, globulin, total protein, aspartate aminotransferase, alanine aminotransferase, and total bilirubin, reflecting impaired plasma protein synthesis, amino acid metabolism, glucose regulation, and bilirubin conjugation. In contrast, gamma-glutamyl transferase, alkaline phosphatase, total bile acids, and cholesterol remained stable, suggesting that the infection predominantly caused hepatocellular rather than cholestatic injury. Histopathological changes were consistent with the biochemical results, showing progressive vacuolar degeneration, inflammatory infiltration, hemorrhage, and hepatocellular necrosis in a dose-dependent manner. Together, these findings provide integrated evidence of liver dysfunction and pathology in C. gariepinus following acute A. hydrophila infection. The identified biomarkers and histological alterations may serve as reliable indicators of disease progression and offer valuable insights for the development of therapeutic interventions, health prognosis, and sustainable management strategies in catfish aquaculture.